On the matrix of rank one over a UFD - Somayeh Hadjirezaei; Somayeh Karimzadeh (Journal of Hyperstructures)
In this paper we characterize all matrices of rank one over a unique factorization domain (UFD). Also we find the Rmodule generated by the rows and the R-module generated by the columns of a matrix of rank one and assert some properties of them.